The Nexus Among Organizational Justice, Job Performance, Job Satisfaction, and Employee Loyalty in S Company of the Museum Exhibition Industry - Zhijian, Li; Ruanggoon, Jirapong; Wana, Chayoot (Science, Technology, and Social Sciences Procedia, 2024)
To comprehend employee loyalty within the museum industry, researchers established 2 objectives: 1) To investigate the impact of organizational justice, job performance, and job satisfaction on employees’ loyalty at S Company in the museum exhibition sector; and 2) To explore the mediating roles of job performance and job satisfaction in the relationship between organizational justice and employee loyalty at S Company in the museum exhibition sector. A quantitative approach was employed to analyze employee loyalty at S Company in the museum exhibition industry. Using random sampling, data were collected from 185 employees based on a predetermined formula. The researchers utilized Structural Equation Modeling (SEM) to analyze the data concerning employee loyalty. The findings revealed that: 1) Organizational justice positively influences job performance and job satisfaction, which, in turn, positively affect employee loyalty; and 2) Job performance and job satisfaction act as mediators in the relationship between organizational justice and employee loyalty. Based on these conclusions and discussions, the researchers recommend creating a conducive environment within the museum exhibition industry to enhance customer experience. Given that employee satisfaction plays a crucial role in this industry, fostering a positive work environment can contribute significantly to the long-term success of museum display enterprises. Committed employees who align with the company’s vision aid in maintaining competitiveness, attracting top talent, and establishing credibility in the marketplace. By promoting organizational justice, organizations can enhance their long-term sustainability and adaptability to changing market demands.